THE EFFECT OF SERVICE QUALITY, BRAND IMAGE AND PROMOTION ON CUSTOMER SATISFACTION AT CV. ABC HARDWARE INDUSTRY MEDAN SUNGGAL - Yessica Andiny Chandra; Friska Rosanti Zega; Helen Aurora; Nirwana Br Bangun; Jarungjung Hutagaol (CV. Radja Publika, 2026)
This study aims to determine and analyze the effect of service quality, brand image, and promotion on customer satisfaction at CV ABC Hardware Industry Medan Sunggal using a quantitative descriptive correlational approach. The sample consisted of 62 respondents selected through simple random sampling using the Slovin formula from customers who made transactions during January–July 2025. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS, including validity, reliability, classical assumption tests, t-test, F-test, and coefficient of determination. The results show that partially service quality (t-value 2.778; sig 0.007), brand image (t-value 4.405; sig 0.000), and promotion (t-value 2.439; sig 0.018) have a significant effect on customer satisfaction, and simultaneously these three variables also have a significant effect with an F-value of 212.456 and sig 0.000. The Adjusted R Square value of 0.912 indicates that 91.2% of the variation in customer satisfaction can be explained by service quality, brand image, and promotion.